Time, memory, and the legacy of Howard Eichenbaum. Issue 3 (11th September 2018) - Ranganath, Charan
Abstract: Over the past 15 years, there has been an explosion of new research on the role of the hippocampus in the representation of information about time in memory. Much of this work was inspired by the ideas and research of Howard Eichenbaum, who made major contributions to our understanding of the neurobiology of episodic memory and the neural representation of time. In this article, I will review evidence regarding the role of time in understanding hippocampal function. This review will cover a broad range of evidence from studies of humans and nonhuman animals with a narrative arc that follows Howard's major discoveries. These studies demonstrate that the hippocampus encodes information in relation to an episodic context, and that time, as well as space, serves to define these contexts. Moreover, the research has shown that the hippocampus can encode temporal, spatial, and situational information in parallel. Building on this work, I present a new framework for understanding temporal structure in human episodic memory. I conclude by outlining current controversies and new questions that must be addressed by the field in the years to come.